Uma escola a céu aberto: a transmissão de saberes no Instituto Arraial do Pavulagem - FAÇANHA, Tainá Maria Magalhães (Universidade Federal do Pará, 2023)
In this research, I focused my attention on the musical transmission practices in the context of the Arraial do Pavulagem Institute - IAPav. In the formative experiences for preparing the arrastões (street parades), which flow like a river into the streets of Belém, it is possible to highlight the way people interact, transmitting their knowledge and building processes of musical transmission. The general objective of this research consists in investigating the transmission of musical knowledge at the Arraial do Pavulagem Institute, considering its influence on the development of a contemporary musical performance. Specifically, my goals were understanding the musical practice of the Arraial do Pavulagem Institute from life narratives; describing the musical practice of the Arraial do Pavulagem Institute and the ways in which musical transmission is multiplied in the workshops, rehearsals and arrastões; and, finally, discussing the ways of learning and teaching music at the Arraial do Pavulagem Institute, pointing out which influences constitute the "pedagogical" aspects of musical transmission. The thesis is built up from a research conducted in three moments: in 2018 and 2019, with an extensive field research that resulted in a vast collection of audiovisual material; in 2020 and 2021, the field research was carried out virtually from the engagement of the community in the social media of IAPav and in the livestreams of Arraial do Futuro that adapted the street parades to the virtual world due to the social distancing required during the Covid-19 pandemic; and after the face-to-face return, in 2022, of the group's activities, which enabled a very unique experience of return to "normality" and the conducting of interviews that are part of the heart of this work. In this regard, this thesis succinctly made it possible to understand that musical transmission in the Arraial do Pavulagem occurs in a systematic manner in the workshops, primarily through orality. From dimensions linked to the daily experiences inside the Institute, whether in conversations with the masters, in the sharing of experiences with colleagues from the Batalhão da Estrela, or in the coexistence of the articulations of the makers of culture that are formed there, whether in political and/or artistic actions. Still, the transmission happens in the performance itself during the arrastões, in the sound fruition in the shows, and in the experience of the audition of the songs.